Investigating the microstructure of plant leaves in 3D with lab-based X-ray Computed Tomography - Mathers, Andrew M; Hepworth, Christopher; Baillie, Alice; Sloan, Jen; Jones, Hannah; Lundgren, Marjorie; Fleming, Andrew; Mooney, Sacha J.; Sturrock, Craig (BioMed Central, 2018)
Background Leaf cellular architecture plays an important role in setting limits for carbon assimilation and, thus, photosynthetic performance. However, the low density, fine structure, and sensitivity to desiccation of plant tissue has presented challenges to its quantification. Classical methods of tissue fixation and embedding prior to 2D microscopy of sections is both laborious and susceptible to artefacts that can skew the values obtained. Here we report an image analysis pipeline that provides quantitative descriptors of plant leaf intercellular airspace using lab-based X-ray Computed Tomography (microCT). We demonstrate successful visualisation and quantification of differences in leaf intercellular airspace in 3D for a range of species (including both dicots and monocots) and provide a comparison with a standard 2D analysis of leaf sections.